Developing Young Learners’ Speaking Skills Through Storytelling Technique (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Everybody, both young learners and teenagers, as well as adults, loves stories, whether these stories are fairy tales, folktales, legends, fables or short stories, because they are based on real-life incidents experienced by learners themselves, therefore implementation of storytelling technique is considered one of the most beneficial approaches for teaching speaking to different age group learners. This technique is a unique way for developing an understanding, respect and appreciation for other cultures, as well as it can promote a positive attitude towards people from different lands, races and religions. Young learners are extremely energetic and have a lot of physical energy, as they play, they learn and practice social skills, including communication and language skills, and stories play a significant role in their language learning process, as well as enhancing their speaking skills.So, this article deals with the benefits of using storytelling techniques in teaching and developing young learner’s speaking skills.